2006
DOI: 10.4049/jimmunol.176.2.1195
|View full text |Cite
|
Sign up to set email alerts
|

Activation of TLR-9 Induces IL-8 Secretion through Peroxynitrite Signaling in Human Neutrophils

Abstract: Bacterial DNA containing unmethylated CpG motifs is emerging as an important regulator of functions of human neutrophil granulocytes (polymorphonuclear leukocytes (PMN)). These motifs are recognized by TLR-9. Recent studies indicate that peroxynitrite (ONOO−) may function as an intracellular signal for the production of IL-8, one of the key regulators of leukocyte trafficking in inflammation. In this study we investigated whether bacterial DNA (CpG-DNA) could induce ONOO− signaling in human PMN. Human whole bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
67
1
4

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 86 publications
(79 citation statements)
references
References 49 publications
7
67
1
4
Order By: Relevance
“…We previously found that pretreatment of neutrophils with bafilomycin A, which inhibits vacuolar H ϩ -ATPase (37) or chloroquine, which accumulates in and increases the pH in endosomes (35), rendered the apoptotic machinery and IL-8 gene transcription in neutrophils unresponsive to CpG DNA (13,24). In this study, we showed that bafilomycin A and chloroquine prevented CpG DNA-induced L-selectin shedding and up-regulation of CD11b/CD18 expression.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…We previously found that pretreatment of neutrophils with bafilomycin A, which inhibits vacuolar H ϩ -ATPase (37) or chloroquine, which accumulates in and increases the pH in endosomes (35), rendered the apoptotic machinery and IL-8 gene transcription in neutrophils unresponsive to CpG DNA (13,24). In this study, we showed that bafilomycin A and chloroquine prevented CpG DNA-induced L-selectin shedding and up-regulation of CD11b/CD18 expression.…”
Section: Discussionmentioning
confidence: 53%
“…In mice, bacterial DNA or synthetic oligodeoxynucleotides (ODNs) 4 containing unmethylated CpG motifs promotes neutrophil accumulation at the primary sites of infection (8, 20 -23). Consistent with enhanced neutrophil trafficking in vivo, CpG DNA enhances neutrophil chemotaxis (12), induces IL-8 release (11,24), triggers L-selectin shedding and up-regulation of CD11b/ CD18 (Mac-1) (11,12), and delays neutrophil apoptosis (13). However, it is not known whether bacterial DNA could promote neutrophil adhesion to endothelial cells, a critical step in neutrophil trafficking into tissues.…”
mentioning
confidence: 99%
“…Of note, despite expression of TLR9 by B cells, pDC, and neutrophils (43,44), addition of bacterial DNA (derived from E. coli) did not induce secretion of cytokines in human whole blood (data not shown and Ref. 48). The kinetics of our early transient LPS tolerance model differ from classical LPS tolerance models in experimental animals, which are characterized by an early cellular-mediated phase, which dissipates after 3-5 days, and a late Ab-mediated phase (6,49).…”
Section: Discussionmentioning
confidence: 99%
“…Studies performed with human neutrophils by József et al (46,47) showed that bacterial DNA moderately delays apoptosis and induces IL-8 secretion through a CpG-and TLR9-dependent mechanism. Their studies were based on results obtained by using endosomal acidification inhibitors such as chloroquine and bafilomycin A and CpG-methylated DNA but did not include the use of TLR9 knockout mice.…”
Section: Discussionmentioning
confidence: 99%